The Influence of Marketing Mix on Consumer Buying Interest at PT. Sinar Sagara Sejahtera Sumedang - Sukmayadi, Sukmayadi (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This study entitled the effect of the marketing mix on consumer buying interest at PT. Sinar Sagara Sejahtera Sumedang. This research uses descriptive method with quantitative analysis techniques, carried out through survey methods. Data collection techniques were analyzed by means of observation and questionnaires. The population taken is the average consumer per year, namely 2,175 people while the sample is calculated using the Slovin formula and the results are 96 respondents. Research data using simple regression analysis, correlation test, coefficient of determination and hypothesis testing. The results of this study indicate that the marketing mix is ​​7,827 (good) with an average of 81.49%, consumer buying interest is 3,769 (good) with an average of 83.5%. Furthermore, the magnitude of the marketing mix relationship to consumer buying interest at PT. Sinar Sagara Sejahtera Sumedang of 0.741 (a fairly strong relationship), and the influence of the marketing mix on consumer interest in PT. Sinar Sagara Sejahtera Sumedang is 54.90% and there are still 45.10% other factors. The results of the calculation of the hypothesis test turned out to be tcount > ttable or 10.7 > 1.66123, it can be said that there is a positive influence between the marketing mix on consumer buying interest at PT.Sinar Sagara Sejahtera Sumedang which is acceptable. To improve the company’s marketing mix strategy, it must pay attention to aspects that can support the improvement of the marketing mix, be it price, product, promotion and place so that consumer interest can occur and consumers decide to buy.